Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Certainly! Let's convert the given Cartesian equation [tex]\( x^2 + y^2 = 2y \)[/tex] into a polar coordinate equation step by step.
1. Recall the polar coordinates relationships:
[tex]\[ x = r \cos(\theta) \][/tex]
[tex]\[ y = r \sin(\theta) \][/tex]
2. Substitute these polar coordinates into the given Cartesian equation [tex]\( x^2 + y^2 = 2y \)[/tex]:
[tex]\[ (r \cos(\theta))^2 + (r \sin(\theta))^2 = 2 \cdot (r \sin(\theta)) \][/tex]
3. Simplify the left side of the equation:
[tex]\[ r^2 \cos^2(\theta) + r^2 \sin^2(\theta) = 2r \sin(\theta) \][/tex]
4. Factor out [tex]\( r^2 \)[/tex] on the left side:
[tex]\[ r^2 (\cos^2(\theta) + \sin^2(\theta)) = 2r \sin(\theta) \][/tex]
5. Recall that [tex]\( \cos^2(\theta) + \sin^2(\theta) = 1 \)[/tex]:
[tex]\[ r^2 \cdot 1 = 2r \sin(\theta) \][/tex]
[tex]\[ r^2 = 2r \sin(\theta) \][/tex]
6. To solve for [tex]\( r \)[/tex], subtract [tex]\( 2r \sin(\theta) \)[/tex] from both sides:
[tex]\[ r^2 - 2r \sin(\theta) = 0 \][/tex]
7. Factor the equation:
[tex]\[ r (r - 2 \sin(\theta)) = 0 \][/tex]
So, the polar equation equivalent to the given Cartesian equation [tex]\( x^2 + y^2 = 2y \)[/tex] is:
[tex]\[ r (r - 2 \sin(\theta)) = 0 \][/tex]
This is the step-by-step process to convert the equation from Cartesian to polar form.
1. Recall the polar coordinates relationships:
[tex]\[ x = r \cos(\theta) \][/tex]
[tex]\[ y = r \sin(\theta) \][/tex]
2. Substitute these polar coordinates into the given Cartesian equation [tex]\( x^2 + y^2 = 2y \)[/tex]:
[tex]\[ (r \cos(\theta))^2 + (r \sin(\theta))^2 = 2 \cdot (r \sin(\theta)) \][/tex]
3. Simplify the left side of the equation:
[tex]\[ r^2 \cos^2(\theta) + r^2 \sin^2(\theta) = 2r \sin(\theta) \][/tex]
4. Factor out [tex]\( r^2 \)[/tex] on the left side:
[tex]\[ r^2 (\cos^2(\theta) + \sin^2(\theta)) = 2r \sin(\theta) \][/tex]
5. Recall that [tex]\( \cos^2(\theta) + \sin^2(\theta) = 1 \)[/tex]:
[tex]\[ r^2 \cdot 1 = 2r \sin(\theta) \][/tex]
[tex]\[ r^2 = 2r \sin(\theta) \][/tex]
6. To solve for [tex]\( r \)[/tex], subtract [tex]\( 2r \sin(\theta) \)[/tex] from both sides:
[tex]\[ r^2 - 2r \sin(\theta) = 0 \][/tex]
7. Factor the equation:
[tex]\[ r (r - 2 \sin(\theta)) = 0 \][/tex]
So, the polar equation equivalent to the given Cartesian equation [tex]\( x^2 + y^2 = 2y \)[/tex] is:
[tex]\[ r (r - 2 \sin(\theta)) = 0 \][/tex]
This is the step-by-step process to convert the equation from Cartesian to polar form.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.